1972
DOI: 10.1037/h0082195
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood education and social class.

Abstract: The events responsible for recent early childhood education programs are explored. It is argued that differences in socio-economic class child rearing practices could account for differences in scholastic competence. It is pointed out how indices of heritability say little about the educability of individuals. Also, it is shown how nursery schooling deployed under Project Head Start was inappropriate for the children of poverty. Finally, it is argued that programs begun during a child's first three years may p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In this regard a study may be highlighted as conducted by Marmot (2004) and according to this study low income and education have been shown to be strong predictors of a range of physical and mental health problems, including respiratory viruses, arthritis, coronary disease, and schizophrenia as their environmental conditions in their workplace, or they begin their work in unpleasant or embarrassing social situation [2]. In an earlier study by Hunt (1972) which highlighted another significant factor of S.E.S. such as education and showed that education gets back seated in poorer areas where only food and safety are priority and the author further showed that in United States youth audiences are particularly at risk for many health and social problems, such as unwanted pregnancies, drug abuse, and obesity [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard a study may be highlighted as conducted by Marmot (2004) and according to this study low income and education have been shown to be strong predictors of a range of physical and mental health problems, including respiratory viruses, arthritis, coronary disease, and schizophrenia as their environmental conditions in their workplace, or they begin their work in unpleasant or embarrassing social situation [2]. In an earlier study by Hunt (1972) which highlighted another significant factor of S.E.S. such as education and showed that education gets back seated in poorer areas where only food and safety are priority and the author further showed that in United States youth audiences are particularly at risk for many health and social problems, such as unwanted pregnancies, drug abuse, and obesity [3].…”
Section: Introductionmentioning
confidence: 99%